Analisis Efek Mitragynine Terhadap Metabolisme Glukosa melalui Uji Toleransi Glukosa (OGTT) dan Uji Toleransi Insulin (ITT) pada Model Tikus Diabetes - Evi Sylvia Awwalia; RA. Hani Faradis; Devyana Dyah Wulandari; Hotimah Masdan Salim (Universitas Ciputra Surabaya, 2026)
Mitragynine is the major alkaloid found in Mitragyna speciosa (kratom) and has been reported to possess various biological activities, including potential effects on glucose metabolism. However, scientific evidence regarding its role in glucose tolerance and insulin sensitivity remains limited. This study aimed to evaluate the effects of methanolic extract of Mitragyna speciosa containing mitragynine on glucose metabolism through the Oral Glucose Tolerance Test (OGTT) and Insulin Tolerance Test (ITT) in experimental animals. Experimental animals were divided into groups consisting of a control and treatment groups receiving methanolic extract of M. speciosa at doses of 15 mg/kg BW and 30 mg/kg BW. Parameters observed included blood glucose levels at different time points following glucose administration (OGTT) and the response to exogenous insulin administration (ITT). Administration of mitragynine extract significantly reduced blood glucose levels compared with the control group in the OGTT, particularly at the 30 mg/kg BW dose. Furthermore, the ITT demonstrated improved insulin sensitivity, with a more rapid decline in blood glucose levels in the treatment groups. These effects showed a dose-dependent pattern, with the higher dose producing more pronounced improvements. Methanolic extract of Mitragyna speciosa containing mitragynine has the potential to enhance glucose metabolism by improving glucose tolerance and increasing insulin sensitivity. These findings suggest that mitragynine could be explored as a potential adjuvant agent in managing glucose metabolism disorders; however, further investigations are needed to elucidate its molecular mechanisms and long-term safety.